Effect of spacing on crop yield and soil nutrient status under poplar based agroforestry system in semi-arid ecosystem - Dhillon, R.S.; Baniwal, R.S.; Bangarwa, K.S.; Bhardwaj, K.K.; Handa, A.K.; kumari, Sushil; Chavan, S.B.; Rizvi, R.H.; Sirohi, Chhavi; Sheokand, R.N. (Indian Journal of Agroforestry, 2020)
The poplar based agroforestry systems of 5×4m, 10×2m and 18×2×2m spacing was established in 2008 in semi arid ecosystem. After eight years, tree height was not affected significantly at different spacings, whereas girth varied significantly among different spacing. The cowpea-wheat and sorghum-berseem crop rotation was followed in poplar based agroforestry system. Results revealed that growth and yield of agricultural crops decreased significantly with the decrease in poplar spacing. The reduction in yield was more severe in kharif crops. The rate of decrease in yield of sorghum fodder and wheat was more under 5×4 m spacing. The mean decrease in the yield of berseem under different spacings of poplar was 31.1% over control (devoid of trees). On an average, the grain yield of wheat decreased up to 51.2% under 5×4m spacing as compared to the sole wheat (4.3 t ha-1). The wheat quality parameters viz. protein content and gluten % was increased with the decrease in spacing of poplar and maximum protein content (10.7%) in wheat was recorded under 5×4 m spacing closely followed by 10×2 m (10.4%) over control. The values of gluten % were also observed highly significantly under different spacings of poplar based agroforestry than sole crop of wheat. Among different spacings of poplar, highest organic carbon (0.76%) build up was recorded in 5×4 m. Soil pH and the electrical conductivity were also lowered from its initial value under different spacings. The available soil N, P and K increased significantly under different spacings of poplar based agroforestry system. The available phosphorus in the soil increased substantially and it was more than two times under poplar based agroforestry system from the initial value.